(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Pandemic conditions have brought changes to various human activities in this world. One of them is learning activities, which usually at school now have to be done at home. because these demands make educational institutions must be able to accommodate the online learning process by preparing an application platform. with the use of this new technology is it acceptable to use it. then the researcher uses the variable perceived of usefulness and perceived ease of use. This research was conducted at 6 private universities in Indonesia randomly and got 233 respondents. The data collective by questionnaire and analysis technique used multiple regression analysis. The results showed that Perceived Usefulness (X1) and Perceived Ease to Use (X2) have a significant effect on Intention to Use (Y) the use of e-learning applications by 43.9% Keywords: Adoption Technology, Online Learning, Pandemic